COLONIZATION OF THE ZHETYSU REGION BY THE RUSSIAN EMPIRE (BASED ON THE WORKS OF I. ZHANSUGUROV) (Journal of history, 2024)
In our research article on «Colonization of Zhetysu Region by the Russian Empire (based on the works of I.Zhansugurov)» attention is paid to the historical works of the talented poet Ilyas Zhansugurov. Ilyas Zhansugurov’s works concerning history, for a long time remained without the attention of readers and researchers. In 2001, journalist Abilkhan Abilasan translated the poet’s works from Arabic to Cyrillic, publishing them in a collection. In our research article on the basis of the historical work of Ilyas Zhansugurov «Russian capture of Zhetysu Region» the policy of the Russian Empire on colonization of Zhetysu Region is scientifically considered, armed resistance of Kazakh tribes is revealed, residents of the same region.The article identified the importance of the poet’s historical works in uncovering the armed resistance of the Kazakh plemps inhabiting the Zhetysu Territory during the period of Russian colonization. Secondly, the works of the poet, who is not a professional historian, establish the accuracy of historical events, specified dates, and the unmistakable and reliable transmission of the actions of historical personalities.Thirdly, the actions and origins of Sybankul Khanchejaula, belonging to the Torah clan, which led the Naiman clan raised against the Russian colony, have been comprehensively revealed. Fourth, the author of the article shows that he was well acquainted with the works of the poet I. Zhansugurov Murat Monkeuly, Mahambet Utemisov, who lived in the XIX century. Fifthly, based on the historical works of I. Zhansugurov, the article highlights topics that will be considered as objects of research in the future: 1) resolute opposition to the Russian occupation of the matai tribe inhabiting the rivers Lepsy and Karatal; 2) resistance of the alban tribe to the Russian invasion; 3) resistance of the dulat tribe to the Russian takeover; 4) influence of the Kokan Khanate in the Zhetysu region during the Russian conquest and Russian-Kokan relations; 5) participation of Kazakhs from the Zhetysu region in the nationalthe liberation uprising led by Kenesary Kasymuly. The article stresses that the study of the rich heritage left by the poet should be carried out not only by writers, but also by historians. This will allow a comprehensive study of the policy of colonization of the Zhetysu region of the Russian Empire, which began in the middle of the 19th century and continued until the first quarter of the 20th century. In addition, the contribution to the field of local studies and the education of the younger generation will be of great importance.